ANALISIS AWAL KEMAMPUAN BERCERITA PADA ANAK USIA 5 - 6 TAHUN - Ika Lestari (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2018)
The ability to tell stories needs to be trained in early childhood to learn to express their thoughts, needs, and emotions. The purpose of the study was to analyze the initial ability of storytelling that is owned by children aged 5-6 years so that it can be taken into consideration in determining the learning media to be made. The place of the study was conducted at Al Iman Kindergarten in East Jakarta from January - December 2016. The research method used was quantitative by using a storytelling ability test that was distinguished by language and non-language aspects. Data analysis techniques are carried out using descriptive statistics. The results of the research are indicators of storytelling abilities derived from language and non-language aspects. Based on the results of the storytelling ability test obtained if most children are still not good in the language and non-language aspects. Recommendations for further research are expected to develop learning media that train childrenâ€™s storytelling skills for the better. References: Berkowitz, D. (2011). Oral storytelling: Building community through dialogue, engagement, and problem-solving. YC Young Children, 66(2), 36-41. https://eric.ed.gov/?id=EJ930387 Djaali & Muljono, (2008). Pengukuran dalam bidang pendidikan. Jakarta: Grasindo. Fekonja-Peklaj, U., MarjanoviÄ-Umek, L., & Kranjc, S. (2010). Childrenâ€™s storytelling: The effect of preschool and family environment. European Early Childhood Education Research Journal, 18(1), 55â€“73.doi:10.1080/13502930903520058 Kervin, L. & Mantei, J. (2016). Digital storytelling: Capturing childrenâ€™s participation in preschool activities. Issues in Educational Research, 26(2), http://www.iier.org.au/iier26/kervin.pdf Lenox, M. F. (2000). Storytelling for young children in a multicultural world. Early Childhood Education Journal, 28(2), 97â€“103. doi:10.1023/a:1009599320835 Maidar G. A. & Mukti U.S. (1988). Pembinaan kemampuan berbicara. Jakarta: Erlangga. Miller, S. & Pennycuff. (2008). The power of story: Using storytelling to improve literacy learning. Journal of Cross-Disciplinary Perspectives in Education, 1(1), 36 â€“ 43. http://wmpeople.wm.edu/asset/index/mxtsch/storytelling Nurgiyantoro, B. (2010). Penilaian pembelajaran bahasa berbasis kompetensi. Yogyakarta: BPFE. PekdoÄŸan, S. (2016). Investigation of the effects of story-based social skills training program on the social skill development of 5-6-year-old children. Education and Science, 41, 183, 305-318. https://eric.ed.gov/?id=ED573653 Schneider, P., Rivard, R., & Debrueil, B. (2011). Does colour affect the quality or quantity of childrenâ€™s stories elicited by pictures?. Child Language Teaching and Therapy, 27, 2-3. https://rehabilitation.ualberta.ca//media/rehabili-tation/faculty-site/departments/csd/documents/enni/bw-colour-final-version.pdf Setiati, L., Sunarto, P. & Setiawan, P. (2011). Komunikasi gambar bercerita pada buku belajar baca anak taman kanak-kanak. ITB J. Vis. Art & Des, 5(1), http://download.portalgaruda.org/article.php?article=312143&val=7392&title=Komunikasi%20Gambar%20Bercerita%20 pada%20Buku%20Belajar%20Baca%20Anak%20Taman%20Kanak-Kanak Silva, M., Strasser, K., & Cain, K. (2014). Early narrative skills in Chilean preschool: Questions scaffold the production of coherent narratives. Early Childhood Research Quarterly, 29, 205â€“213 http://repositorio.uchile.cl/bitstream/han-dle/2250/124436/Early-narrative-skillsin-Chilean-preschool-Questions-scaffoldthe-production-of-coherent-narratives.pdf?sequence=1 Stadler, M. A., & Ward, G. C. (2006). Supporting the Narrative Development of Young Children. Early Childhood Education Journal, 33(2), 73â€“80. doi:10.1007/s10643-005-0024-4 Tayler, C. (2015). Learning in early childhood: Experiences, relationships and â€˜learning to be.â€™ European Journal of Education. 50(2). http://onlinelibrary.wiley.com/doi/10.1111/ejed.12117/full Whorrall, J., & Cabell, S. Q. (2015). Supporting Childrenâ€™s Oral Language Development in the Preschool Classroom. Early Childhood Education Journal, 44(4), 335â€“341. doi:10.1007/s10643-015-0719-0 Willis, C. A., & Schiller, P. (2011). Preschoolersâ€™ social skills steer life success. YC young children, 66(1), 42-49. CCCNS NoG-090-Wil/YC. Wright, C., Diener, M. L., & Kemp, J. L. (2013). Storytelling dramas as a community building activity in an early childhood classroom. Early Childhood Education Journal, 41, 197â€“210. doi: http://dx.doi.org/10.4135/9781483340333.n391